Laboratory evidence for the formation of hydrogenated fullerene molecules - Thrower, J. D. (Proc Int Astron Union, 2019)
Experimental evidence for the formation of hydrogenated fullerene molecules is presented. Films of C(60) were grown on a highly oriented pyrolytic graphite (substrate) and exposed to a beam of deuterium atoms. Thermal desorption combined with mass spectrometry was used to determine the deuterated fullerene products formed, revealing a maximum degree of deuteration corresponding to C(60)D(36). Release of D(2) from the deuterated C(60) film occurs at a much higher temperature than for D-saturated graphite.